Optimización en la elaboración de galletas utilizando harina de cañihua (Chenopodium pallidicaule), kiwicha (Amaranthus caudatus) y quinua (Chenopodium quinoa) - Coila Lasteros, Rocio Angelica (2019)
The objective of this work was the optimization in the elaboration of cookies of high acceptability which were made with a substitution of 0 -15% of hemp flour, kiwicha flour and quinoa flour in wheat flour, for this it was done 10 different treatments which were done as follows: first the raw material and supplies were received, then weighed, kneaded, rolled, molded, then we went to the baking that is 140 ° C * 10min then we wait 30 min I cooled and finally stored in airtight bags, the evaluation of the overall acceptability of the cookie was made by 60 untrained panelists. For the optimization a Simplex Mix Design with Extended Centroid was used. In this sense, ten types of biscuits were evaluated, finding that the optimization of general acceptability is achieved, when the components are in the following ranges: 10.8% -15% quinoa flour, 0% -5.4% cañihua flour and 0% - 3.3% kiwicha flour and at the same time to this best treatment We performed analysis of humidity (%), protein (%), fat (%) and ash (%) which had a value of 1.18%, 11.42%, 4.38%, 1.41% respectively.